Servant leaders as underestimators: theoretical and practical implications. Issue 2 (3rd April 2017) - Sousa, Milton; van Dierendonck, Dirk
Abstract : Purpose: The purpose of this paper is to provide a new interpretation of underestimation for the particular case of servant leadership, contending the ideas that underestimation is caused by lack of self-awareness or low self-esteem, and that self-other agreement is a necessary condition for self-awareness. Additional reflections are provided on the development of servant leadership in organizations. Design/methodology/approach: A revision of the self-other agreement literature was done, with a focus on underestimation. The theoretical foundations of servant leadership were analysed. The main hypothesis was derived, including a set of supporting propositions. An empirical study was conducted based on a polynomial regression and 3D surface analysis, including 36 managers and 160 followers. Findings: Underestimation was the strongest predictor of servant leadership effectiveness in generating psychological empowerment amongst followers. The theoretical revision provides arguments to support the claim that servant leaders underestimate themselves because of their humility and valuing of others. Practical implications: With the increasing adoption of servant leadership, this study supports the need to develop specific processes for detecting, assessing, and developing servant leaders in organizations. Additional care is necessary on the interpretation of self-other ratings through 360-degree instruments in light of the leadership model being considered. Originality/value: It is the first empirical study within the self-other leadership agreement that incorporates servant leadership. It provides an alternative explanation of underestimation for servant leaders. The paper also provides a reflection on the practical implications of underestimation for developing servant leadership in organizations.